Collaborative Governance of Jember Customs in Combating the Distribution of Illegal Cigarettes - Muh. Ali Imron; Edy Wahyudi; Suyani Indriastuti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The circulation of illegal cigarettes in Jember Regency has become a complex public policy issue due to the region’s strategic position as a tobacco-producing area and the increasing distribution of untaxed cigarettes that cause state revenue losses and unhealthy business competition. Previous studies have predominantly emphasized legal enforcement and taxation aspects, while limited research has examined collaborative governance involving multiple stakeholders in combating illegal cigarette distribution at the local level. This study aims to analyze the implementation of collaborative governance by Jember Customs in combating the distribution of illegal cigarettes in Jember Regency. This research employed a qualitative descriptive method with data collected through interviews, observations, and documentation involving Customs officers, local government, Satpol PP, law enforcement agencies, business actors, and community representatives. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The results indicate that collaborative governance has been implemented through joint operations, public socialization, supervision, and inter-agency coordination supported by the Tobacco Excise Revenue Sharing Fund (DBHCHT). However, challenges remain in limited human resources, broad supervisory areas, and low public awareness. This study concludes that collaborative governance strengthens inter-agency synergy and improves the effectiveness of illegal cigarette control in Jember Regency.